On the Electronic Structure of 2H-MoS2: Correlating DFT Calculations and In-Situ Mechanical Bending on TEM - Ramos Murillo, Manuel Antonio (2022)
We present a systematic density functional theory study to determine the electronic structure of bending 2H-MoS2 layers up to 75deg using information from in-situ nanoindentation TEM observations. The results from HOMO/LUMO and density of states plots indicate a metallic transition from the typical semiconducting phase, near Fermi energy level (EF) as a function of bending, which can mainly occur due to bending curvatures inducing a stretching and contracting of sulfur-sulfur chemical bonds located mostly over basal (001)-plane; furthermore, molybdenum ions play a major role in such transitions due to reallocation of their metallic d-character orbitals and the creation of “free electrons”, possibly having an overlap between Mo-dx2-y2 and Modz2 orbitals. This research on the metallic transition of 2H-MoS2 allows us to understand the high catalytic activity for MoS2 nanostructures as extensively reported in the literature.